2006
DOI: 10.1159/000091788
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poststroke Dementia: Results of a Hospital-Based Study in Poland

Abstract: Dementia affects up to 30% of stroke survivors 3 months after stroke. The goal of this study was to determine the risk factors of poststroke dementia (PSD) in a cohort of consecutive stroke patients in Poland. A standard stroke evaluation was conducted on admission in 220 consecutive patients with ischemic/hemorrhagic stroke after excluding 30 (12%) patients with prestroke dementia. After 3 months, the survivors completed a comprehensive neuropsychological examination. The DSM-IV definition was used for diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 50 publications
0
44
0
1
Order By: Relevance
“…Fifteen abstracts were excluded because the result no associated with poststroke dementia, thirteen articles cannot calculate the data for the relative risks of dementia in stroke patients. The remaining 8 articles 20,21,23,[26][27][28][29][30] selected by the selection criteria can be calculated to identify the relative risks of dementia, as shown in Figure 1. Table 1 shows the demographic details of hospital-based and population-based studies of dementia after stroke such as study design, and methods used to measure dementia in all the publications that were relevant to the eligible hospital-based and population-based studies of dementia after stroke.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen abstracts were excluded because the result no associated with poststroke dementia, thirteen articles cannot calculate the data for the relative risks of dementia in stroke patients. The remaining 8 articles 20,21,23,[26][27][28][29][30] selected by the selection criteria can be calculated to identify the relative risks of dementia, as shown in Figure 1. Table 1 shows the demographic details of hospital-based and population-based studies of dementia after stroke such as study design, and methods used to measure dementia in all the publications that were relevant to the eligible hospital-based and population-based studies of dementia after stroke.…”
Section: Resultsmentioning
confidence: 99%
“…First, demographics and clinical characteristics of patients which showed increasing age associated with an increased risk of poststroke dementia in most studies. 16,[18][19][20][21]23,25,32 Adding demographics factors showed that the risk of incident dementia elevated in relation to older age especially > 80 years (RR 4.66, 95%CI; 2.36 to 9.22) and age 70 to 79 years (RR 2.68, 95%CI; 1.52 to 4.74) versus age 60 to 69 years. 28 33 Previous mental decline was the correlation of dementia in logistic regression analysis (OR 1.20, 95%CI; 1.10 to 1.40).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations